Optical Active Meta-Surfaces, -Substrates, and Single Quantum Dots Based on Tuning Organic Composites with Graphene - Romero, Marcelo Ricardo (2024)
In this communication, the design and fabrication of optical active metamaterials were developed by the incorporation of graphene and joining it to different substrates with variable spectroscopical properties. It focuses on how graphene and its derivatives could generate varied optical setups and materials considering modified and enhanced optics within substrates and surfaces. In this manner, it is discussed how light could be tuned and modified along its path from confined nano-patterned surfaces or through a modified micro-lens. In addition to these optical properties generated from the physical interaction of light, it should be added that the non-classical light pathways and quantum phenomena could participate. In this way, graphene and related carbon-based materials with particular properties, such as highly condensed electronics, pseudo-electromagnetic properties, and quantum and luminescent properties, could be incorporated. Therefore, the modified substrates could be switched by photo-stimulation with variable responses depending on the nature of the material constitution. Therefore, the optical properties of graphene and its derivatives are discussed in these types of metasurfaces with targeted optical active properties, such as within the UV, IR, and terahertz wavelength intervals, along with their further properties and respective potential applications.